2020
DOI: 10.1002/fsn3.1818
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine and homocysteine as biomarker of various diseases

Abstract: Cysteine and homocysteine (Hcy), both sulfur‐containing amino acids (AAs), produced from methionine another sulfur‐containing amino acid, which is converted to Hcy and further converted to cysteine. This article aims to highlight the link between cysteine and Hcy, and their mechanisms, important functions, play in the body and their role as a biomarker for various types of diseases. So that using cysteine and Hcy as a biomarker, we can prevent and diagnose many diseases. This review concluded that hyperhomocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(105 citation statements)
references
References 76 publications
1
101
1
2
Order By: Relevance
“…Cysteine, a proteinogenic non-essential sulfur-containing AA, can be sourced from the diet or produced via methionine degradation [ 14 ]. In the human body, cysteine is involved in lipid, keratin and iron–sulfur (a constituent of skeletal muscle) biosynthesis and represents a precursor of the antioxidant glutathione and of the coenzyme A, which is involved in cellular oxidative stress [ 14 ]. Higher serum cysteine levels have been reported in metabolic syndrome and obesity [ 15 ], and have been hypothesized to have an insulin-like action at the adipocyte level [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine, a proteinogenic non-essential sulfur-containing AA, can be sourced from the diet or produced via methionine degradation [ 14 ]. In the human body, cysteine is involved in lipid, keratin and iron–sulfur (a constituent of skeletal muscle) biosynthesis and represents a precursor of the antioxidant glutathione and of the coenzyme A, which is involved in cellular oxidative stress [ 14 ]. Higher serum cysteine levels have been reported in metabolic syndrome and obesity [ 15 ], and have been hypothesized to have an insulin-like action at the adipocyte level [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almost 3% of physiological levels of HCY circulate freely in the body in bound form with other molecules or in disulfide form [ 30 , 31 ]. The majority of HCY in the plasma is in disulfide form and is oxidized by reacting with other molecules that contain free thiol groups such as albumin, and the remaining exists as a reduced form.…”
Section: Physiological Role Of Homocysteinementioning
confidence: 99%
“…Homocysteine is a low-molecular-weight thiol that has a non-specific effect on cells. It is a molecule with a wide range of activities in the human body [ 15 ], and the number of disorders leading to various diseases associated with the state of hyperhomocysteinemia is quite high [ 17 , 18 ]. From a social point of view [ 19 , 20 ], the two most important groups of diseases associated with disorders of homocysteine metabolism are diseases of the nervous system, especially those of neurodegenerative etiology [ 10 ], and cardiovascular diseases of thrombotic etiology [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effective lowering of homocysteine levels appears to be a promising mechanism to prevent redox imbalance and to decrease the occurence of neurodegenerative and thromboembolic diseases, often coexisting, especially in the elderly. Since the metabolism of low -molecular-weight thiols depends on the efficient operation of a number of enzymes, the maintenance of the appropriate concentration of the cofactors (folic acid, vitamins B6 and B12) of these enzymes should be a promising way to keep the state of normohomcysteinemia [ 17 , 18 , 29 , 30 ]. Unfortunately, in some studies, food fortification with the mentioned cofactors has not been shown to effectively restore physiological levels of homocysteine [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%